Fungsi Pengawasan Kepala Ruangan Terhadap Kinerja Perawat Pelaksana Dalam Penerapan Asuhan Keperawatan - Nurul Fuady Fitryani Ahmad; Andi Nursiah; Idris Idris (Lembaga Penelitian dan Pengabdian Masyarakat Akademi Keperawatan Sandi Karsa (Merger) Politeknik Sandi Karsa, 2023)
The Head of the Department, also known as a nurse manager, is responsible for monitoring the quality of care, addressing workforce issues, and ensuring effective performance. One of the roles of the Head of the Department is to act as a leader in the Department, controlling and evaluating the implementation of predetermined nursing care, as well as organizing and coordinating all activities in the ward through collaboration with other staff members. This study aims to determine the relationship between the Head of the Department's supervisory function and staff nurses' performance in delivering nursing care. The research design used is descriptive-analytical with a cross-sectional approach, with a sample size of 36 individuals selected using a purposive sampling technique. Data collection is done using a questionnaire. This study uses the Chi-Square test with Fisher's exact test correction at a significance level of α=0.05. The research findings indicate a significant relationship between the Head of the Department's supervisory function and staff nurses' performance in delivering nursing care (p=0.000). It can be concluded that there is a correlation between the supervisory function of the Head of the Department and the performance of staff nurses in implementing nursing care. Hospital policymakers should further enhance the leadership skills of the Head of the Department through nursing management training.